2014
DOI: 10.7162/s1809-97772013000300009
|View full text |Cite
|
Sign up to set email alerts
|

Audiological outcomes of cochlear implantation in Waardenburg Syndrome

Abstract: Summary Introduction: The most relevant clinical symptom in Waardenburg syndrome is profound bilateral sensorioneural hearing loss. Aim: To characterize and describe hearing outcomes after cochlear implantation in patients with Waardenburg syndrome to improve preoperative expectations. Method: This was an observational and retrospective study of a series of cases. Children who were diagnosed with Waardenburg syndrome and who received a multichannel cochlear implant between March 1999 and July 2012 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 12 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…All studies were published between 2000 and 2022. Study characteristics are summarized in Table 1 15,24–38 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies were published between 2000 and 2022. Study characteristics are summarized in Table 1 15,24–38 …”
Section: Resultsmentioning
confidence: 99%
“…The rationale for early implantation is based on there being a period of maximal neural plasticity in the auditory pathways which ends at around age 3.5 39,40 . This was supported by Magalhaes et al, who found that in their cohort children who had later implantation after the age of three had worse hearing and speech outcomes following CI, these children also had later initial fitting of hearing aids and aural rehabilitation 26 . Conversely, Amirsalari et al, found that age at implantation had no significant effect on hearing and speech outcomes however, this may influenced by their small study population 29 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is confirmed that outcomes of cochlear implant in WS children are similar to other non-syndromic SNHL children [ 24 26 ]. It is also suggested that patients who received early intervention show a better hearing and language skills [ 27 ]. However few studies have identified the intervention time and the outcome of the cochlear implants.…”
Section: Discussionmentioning
confidence: 99%